MANAJEMEN SISTEM INFORMASI PENDIDIKAN DALAM PENINGKATAN KINERJA TENAGA KEPENDIDIKAN DI MTsN 2 JOMBANG - Lailatin Nazulah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This background begins with researchers’ anxiety regarding the role of technology in the existing educational information sytem which has entered a new era but has not been balanced with an increase in human resources to utilize information systems in increasing educational personnel. From the problems above, the author researched the Management of Educational Information System in Improving the Performance of Education Personnel at MTsN 2 Jombang. The research focus is: 1) How is the management of educational information system at MTsN Jombang? 2) How will the performance of education staff at MTsN 2 Jombang be improved? 3) How does educational information system management improve the performance of educational staff at MTsN 2 Jombang. The research uses a qualitative research approach. The data collection techniques use observation, interviews, documentation. Data analysis techniques use: Data Collection, Data Reduction, Data Presentation, and drawing conclusions. Checking the validity of the data by: (1) Credibility Test: a. Extension of Observation, b. Increased Perseverance, c. Triangulation, d. Conduct Membercheck.The research results show that: 1) Management of the education information system has been implemented well and according to existing procedures, has been regulated by the head of the operator, with the existence of an education information system at MTsN 2 Jombang to make it easier to find information about MTsN 2 Jombang through the educational information system. Already available. 2) Improving the performance of educational staff has been carried out well, with the presence of educational staff it can improve performance in preparing programs to improve existing educational staff at MTsN 2 Jombang. 3) Educational information system management in improving the performance of educational staff certainly has an important role in improving the performance of educational staff in schools. Because the existence of an educational information system can help the performance process of educational staff at MTsN 2 Jombang.